Postsynaptic FMRP Regulates Synaptogenesis In Vivo in the Developing Cochlear Nucleus - Wang, Xiaoyu (J Neurosci, 2018)
A global loss of the fragile X mental retardation protein (FMRP; encoded by the Fmr1 gene) leads to sensory dysfunction and intellectual disabilities. One underlying mechanism of these phenotypes is structural and functional deficits in synapses. Here, we determined the autonomous function of postsynaptic FMRP in circuit formation, synaptogenesis, and synaptic maturation. In normal cochlea nucleus, presynaptic auditory axons form large axosomatic endbulb synapses on cell bodies of postsynaptic bushy neurons. In ovo electroporation of drug-inducible Fmr1-shRNA constructs produced a mosaicism of FMRP expression in chicken (either sex) bushy neurons, leading to reduced FMRP levels in transfected, but not neighboring nontransfected, neurons. Structural analyses revealed that postsynaptic FMRP reduction led to smaller size and abnormal morphology of individual presynaptic endbulbs at both early and later developmental stages. We further examined whether FMRP reduction affects dendritic development, as a potential mechanism underlying defective endbulb formation. Normally, chicken bushy neurons grow extensive dendrites at early stages and retract these dendrites when endbulbs begin to form. Neurons transfected with Fmr1 shRNA exhibited a remarkable delay in branch retraction, failing to provide necessary somatic surface for timely formation and growth of large endbulbs. Patch-clamp recording verified functional consequences of dendritic and synaptic deficits on neurotransmission, showing smaller amplitudes and slower kinetics of spontaneous and evoked EPSCs. Together, these data demonstrate that proper levels of postsynaptic FMRP are required for timely maturation of somatodendritic morphology, a delay of which may affect synaptogenesis and thus contribute to long-lasting deficits of excitatory synapses. SIGNIFICANCE STATEMENT Fragile X mental retardation protein (FMRP) regulates a large variety of neuronal activities. A global loss of FMRP affects neural circuit development and synaptic function, leading to fragile X syndrome (FXS). Using temporally and spatially controlled genetic manipulations, this study provides the first in vivo report that autonomous FMRP regulates multiple stages of dendritic development, and that selective reduction of postsynaptic FMRP leads to abnormal development of excitatory presynaptic terminals and compromised neurotransmission. These observations demonstrate secondary influence of developmentally transient deficits in neuronal morphology and connectivity to the development of long-lasting synaptic pathology in FXS.